2013
DOI: 10.1186/ar4136
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of coronary microcirculation abnormalities in systemic sclerosis: a prospective study to evaluate the role of non-invasive tests

Abstract: IntroductionMicrocirculation dysfunction is a typical feature of systemic sclerosis (SSc) and represents the earliest abnormality of primary myocardial involvement. We assessed coronary microcirculation status by combining two functional tests in SSc patients and estimating its impact on disease outcome.MethodsForty-one SSc patients, asymptomatic for coronary artery disease, were tested for coronary flow velocity reserve (CFR) by transthoracic-echo-Doppler with adenosine infusion (A-TTE) and for left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
8
17
1
Order By: Relevance
“…We believe that these data are important because they highlight the benefit of periodic cardiac evaluation of CFR in this subgroup, particularly in view of the negative prognostic significance of a reduced CFR, as shown by Vacca et al 18 We confirm the findings of Vacca et al relative to the greater prevalence of reduced CFR in dcSSc than in lcSSc. Compared with the latter study, however, we used a more conservative cutoff value of CFR (ie, ≤2.0 instead of ≤2.5 previously used by Vacca et al).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We believe that these data are important because they highlight the benefit of periodic cardiac evaluation of CFR in this subgroup, particularly in view of the negative prognostic significance of a reduced CFR, as shown by Vacca et al 18 We confirm the findings of Vacca et al relative to the greater prevalence of reduced CFR in dcSSc than in lcSSc. Compared with the latter study, however, we used a more conservative cutoff value of CFR (ie, ≤2.0 instead of ≤2.5 previously used by Vacca et al).…”
Section: Discussionsupporting
confidence: 81%
“…18 Our results, however, highlight the importance of early evaluation of CFR in these patients for prognostic stratification. In fact, the dcSSc patients in our study had a shorter disease duration than in those with lcSSc (5.43±3.16 years vs. 15.83±12.99 years, P=0.02).…”
Section: Discussioncontrasting
confidence: 41%
“…The SSc patients had a significantly lower CFR than controls, Finally, Vacca et al [36] have very recently confirmed our data in a group of 41 patients with SSc who were asymptomatic for CAD using transthoracic Doppler echocardiography with adenosine infusion to study the microcirculation and dobutamine stress echocardiography to search for left ventricular wall motion abnormalities. CFR was reduced in 19 SSc patients, and 16 showed wall motion abnormalities.…”
Section: Cfr In Systemic Sclerosis (Ssc)supporting
confidence: 68%
“…Introduction associated with the worse survival, but, given present rarity of renal crisis, cardiopulmonary involvement is now accounting for much of the mortality in patients with SSc [5][6][7][8]. However, survival rate may vary across countries being influenced by several factors such as ethnicity, national income, and healthcare programs [9,10].…”
mentioning
confidence: 99%